2006
DOI: 10.1108/02634500610711897
|View full text |Cite
|
Sign up to set email alerts
|

Can the building of trust overcome consumer perceived risk online?

Abstract: Purpose -To explore the role of trust and risk in consumers' apparent reluctance to convert from internet browsers to potential online purchasers. To consider how marketing planners in that environment can devise strategies that balance perceptions of risk against perceptions of trustworthiness. Design/methodology/approach -The literatures of trust and risk were reviewed, with a focus on internet usage and online buying. Six components of organisational trust are used as the framework for a discussion of perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(98 citation statements)
references
References 50 publications
4
69
0
7
Order By: Relevance
“…Given that the purchase probability and purchase intentions of a consumer are raised by a reduction in the perceived risk, it can be clearly seen that a negative association exists between the perceived risk and purchase intentions [39,40]. The previous literature indicates that the perceived risk negatively affects customer purchase intentions [40,41]. Chen and Chang (2012) [42] showed that the perceived risk and purchase intentions have a negative causality with trust, meaning that if enterprises wish to increase consumers' purchase intentions, they should lower products' perceived risk and increase confidence in the products.…”
Section: Relationship Between Perceived Risk and Purchase Intentionsmentioning
confidence: 99%
“…Given that the purchase probability and purchase intentions of a consumer are raised by a reduction in the perceived risk, it can be clearly seen that a negative association exists between the perceived risk and purchase intentions [39,40]. The previous literature indicates that the perceived risk negatively affects customer purchase intentions [40,41]. Chen and Chang (2012) [42] showed that the perceived risk and purchase intentions have a negative causality with trust, meaning that if enterprises wish to increase consumers' purchase intentions, they should lower products' perceived risk and increase confidence in the products.…”
Section: Relationship Between Perceived Risk and Purchase Intentionsmentioning
confidence: 99%
“…For example, Tan (1999) and Donthu and Garcia (1999) asserted that because online buyers are unable to actually confirm product quality during the shopping process, they have a higher level of perceived risk. Harridge-March (2006) pointed out that the risk in online transactions stems from factors such as opportunism exhibited by anonymous trading partners, sellers obtaining personal information, and the inability of the buyer to actually inspect the product. Featherman, Valacich, and Wells (2006) found that when physical service procedures were digitalized to become online electronic services, the perceived artificiality increased the perceived risk of these electronic services.…”
Section: Perceived Riskmentioning
confidence: 99%
“…Despite all the facts, uncertainty and fears of opportunism still characterize the online context, and varying degrees of consumer acceptance and engagement in the use of e-commerce have been observed [9]. This research study describes the factors important for development of A C C E P T E D M A N U S C R I P T 3 e-commerce acceptance by individual consumers.…”
Section: Introductionmentioning
confidence: 96%